Morfometria e incremento de Cordia trichotoma (Vell.) Arráb. ex Steud. na região central do Rio Grande do Sul - Vuaden, Elisabete (2013)
This work aimed to evaluate the morphology and describe the growth of competing and free individual trees of Cordia trichotoma (Vell.) Arráb. ex Steud. The study of free from competition trees was held in the Central region of the state of Rio Grande do Sul, in the cities of Santa Maria and Silveira Martins, and trees under competition were measured in the Campo de Instrução do Ministério do Exército of Santa Maria - CISM and also in Silveira Martins. Competing and free trees larger than 5 centimeters of dbh were numbered and its dendrometric, morphometric and qualitative were measured. The increment data of the last 4 years was obtained from two increment cores collected using Pressler borer. Competition between trees in the forest was calculated based on the number of trees per hectare obtained from the methodologies of Spurr, Bitterlich and Prodan. The louro-pardo trees growing free of competition, has diameter at breast height, crown diameter and the salience index similar to the developed under competition. Under competition, this species invests more in total height, commercial height and height of the crown, however, has less crown length, lower crown percentage and index scope. The louros growing free of competition have periodic annual diameter increment (IPAd) and basal area (IPAg) significantly higher than those under competition. The IPAg this species of free of tree competition can be predicted by dbh, crown factor (fac) and crown density (dec) by two different models, but the model that best fits the data was: IPAg = 0.6665. and 0.0725. (fac.dec). dbh, which considers the fac and dec as discrete variables to determine the slope. The IPAg of louro-pardo under competition can be predicted by the estimated increment from free of competition trees and subtracting the estimated difference between the increments of louros under and free of competition: IPAg = [(0,6665 e 0,0725. (fac.dec) . dap)] [562,28. (N(GBit))-0,585]. The model ln IPAg = 0,5456 . ln dap + 0,1412 . (fac . dec) - 0,00008905 . N(GBit) which has no relationship to the previous model can be used as well, to estimate the increment for louro-pardo under competition, with some advantages over the previous one.